Arborização urbana e percepção ambiental: uma análise descritiva em dois bairros de Natal / RN. - Souza, Mariluce dos Santos (2008)
The current paper aims to check the environmental population perception of the two east side districts of Natal / RN (Rocas and Petrópolis) on its afforestation. The issues related to the environmental perception and afforestation of cities are gaining prominence in the many different areas of knowledge. However, the approaches and methodologies that are following an analytical perspective that by the rule aimed an policy of spatial planning not always responds to the aspirations and needs of the urban population. The research has been consisted of a preliminary survey, collecting data through the representative population of the neighborhoods in Petrópolis and Rocas, which were applied 210 forms (with the households), 130 in the neighborhood of Rocas and 80 in Petrópolis, which corresponds to 5% of the total households of the two districts, using as indicators, among many others, the income, the level of education and the environmental characteristics of the neighborhood. Through analysis sample was possible to verify that Petrópolis neighborhood that, 68% of interviewee believes their lives in the neighborhood where good and only 2% consider bad, in Rocas neighborhood, 57% considered life in his neighborhood good and only 5% consider bad. When asked about the main characteristics that remind the neighborhood Petrópolis, 90% of residents mentioned that one of its main advantages are the means of transport available, followed by 82% who quoted the ventilation as one of the main benefits of the neighborhood. In Rocas neighborhood, items mentioned by residents, were the ventilation with 47% of all interviewee and 32% said that peace is one of the most positive point of the neighborhood. From the description of some of the environmental needs of the neighborhoods Petrópolis and Rocas, it is possible to infer that environmental issues in general, and afforestation are always present in the speech of the residents, even indirect way, it shows that regardless of the education degree or the income, environmental quality is present as one of the basic needs of urban areas with implications both in the personal and social life as of its inhabitants.